2018
DOI: 10.1021/acs.jpcc.8b03308
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Properties of Monolayer SnS–Metal Contacts

Abstract: Two-dimensional semiconducting SnS is expected to have great potential for application in nanoelectronics. By using both ab initio electronic structure calculations and more reliable quantum transport simulations, we systematically explored the interfacial properties of monolayer (ML) SnS in contact with a series of metals (Ag, Al, Au, Pd, Cu, and Ni) for the first time. According to the adsorption level, three categories are found: strong adsorption is found in ML SnS–Pd and Ni contacts; medium adsorption is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 66 publications
0
14
0
Order By: Relevance
“…17 ML SnS with Ag, Al, Au, Pd, Cu, and Ni electrodes are also simulated. 18 However, since ML MXs have significant anisotropic properties, there is still a lack of systematic comparative study of the performance of MXs in contact with metal electrodes along with armchair and zigzag directions, and the prediction of interfacial properties is very helpful in developing 2D MXs transistors.…”
Section: Introductionmentioning
confidence: 99%
“…17 ML SnS with Ag, Al, Au, Pd, Cu, and Ni electrodes are also simulated. 18 However, since ML MXs have significant anisotropic properties, there is still a lack of systematic comparative study of the performance of MXs in contact with metal electrodes along with armchair and zigzag directions, and the prediction of interfacial properties is very helpful in developing 2D MXs transistors.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we use six layers of bulk metal atoms (Au, Ag, Pd, Pt, Ir, and Ni in the (111) orientation) to simulate the metal surface because six-layer metal atoms can achieve convergence of the contact system according to the convergence tests accomplished in the previous studies, as shown in Figure a–f. Particularly, these orientations correspond to the close-packed faces. The lattice constant of ML TiS 3 was strained to match the fixed lattice constants of the metal surface to achieve the smallest possible lattice match . In the light of finding a common supercell with minimal strain, the software ATK can scan all possible repetitions and rotations of the two surfaces, we chose the appropriate orientation of the six metallic planes respect to the plane of the ML TiS 3 .…”
Section: Resultsmentioning
confidence: 99%
“…For 2D/3D heterostructure composed of bulk metals (e.g., Sc, Ti, Ag, Cu, Au, Pd, Pt, Cr, Ni, etc.) in contact with TMDC monolayers of WS 2 , 178 WSe 2 , 192 WTe 2 , 193 MoS 2 , 175,194 MoSe 2 , 195 and with black phosphorene, 196 and black‐phosphorene‐analogues such as SnS 197 and SnSe 198 are studied using DFT and quantum transport simulations. Rich contact phenomena, such as the formation of n ‐type and p ‐type Schottky contacts, ohmic contacts, and the strong metalization of the 2D semiconductors by contacting metals are identified in these materials.…”
Section: First‐principle Density Functional Theory Simulation Of Electrical Contacts To 2d Materialsmentioning
confidence: 99%
“…Beyond TMDCs, black phosphorene 196 and black‐phosphorene‐analogues, such as SnS 197 and SnSe, 198 are also extensively studied. For this class materials, strong metalization and substantial Fermi level pinning effect are identified.…”
Section: First‐principle Density Functional Theory Simulation Of Electrical Contacts To 2d Materialsmentioning
confidence: 99%
See 1 more Smart Citation